2017
DOI: 10.3389/fphys.2017.00283
|View full text |Cite|
|
Sign up to set email alerts
|

RNA-Seq Comparison of Larval and Adult Malpighian Tubules of the Yellow Fever Mosquito Aedes aegypti Reveals Life Stage-Specific Changes in Renal Function

Abstract: Introduction: The life history of Aedes aegypti presents diverse challenges to its diuretic system. During the larval and pupal life stages mosquitoes are aquatic. With the emergence of the adult they become terrestrial. This shifts the organism within minutes from an aquatic environment to a terrestrial environment where dehydration has to be avoided. In addition, female mosquitoes take large blood meals, which present an entirely new set of challenges to salt and water homeostasis.Methods: To determine diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 60 publications
1
24
0
Order By: Relevance
“…aegypti demonstrated that refractory hemolymph is inhibitory to development of B. malayi (53). Regardless of whether larvae are restricted autonomously by activation of Toll signaling in their site of development or by activation of Toll signaling in another tissue, existing suitable tissue-selective expression systems for fat body (26) or indirect flight muscle (54), or newly generated expression systems for the Malpighian tubules identified using the transcriptomic information generated in this study and others (55), could be used to promote tissue-specific activation.…”
Section: Discussionmentioning
confidence: 99%
“…aegypti demonstrated that refractory hemolymph is inhibitory to development of B. malayi (53). Regardless of whether larvae are restricted autonomously by activation of Toll signaling in their site of development or by activation of Toll signaling in another tissue, existing suitable tissue-selective expression systems for fat body (26) or indirect flight muscle (54), or newly generated expression systems for the Malpighian tubules identified using the transcriptomic information generated in this study and others (55), could be used to promote tissue-specific activation.…”
Section: Discussionmentioning
confidence: 99%
“…AaeZIP11 transcripts were also found to be enriched in the Malpighian tubules, particularly following a bloodmeal, suggesting a potential role in excretion. As the key organ for insect excretion and detoxification, Malpighian tubules may play a critical role in excretion of excess iron accumulated in the hemolymph (Folwell et al, 2006 ; Beyenbach et al, 2010 ; Li et al, 2017 ). As a candidate exporter, AaeZIP11 may function in concert with AaeZnT7 (candidate importer) to transfer iron from the hemolymph to the MT lumen for excretion, and we are actively investigating this possibility.…”
Section: Discussionmentioning
confidence: 99%
“…The differences in expression of AaAQP1 between larvae and adults is therefore not surprising. Substantial differences in the transcriptome of MTs of mosquito larvae and adults have been reported and suggested to be related to the different functions the MTs need to play in larvae versus adults [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…An alternative, or additional, function of AaAQP4 and AaAQP5 on the basal membrane is for trehalose uptake from the hemolymph to support metabolic functions of MTs cells as suggested for the GC (see above). In addition, AaAQP2 transcript levels in MTs of larvae are substantially high and warrant a thorough investigation at the protein level when an antibody is available [ 15 , 47 ].…”
Section: Discussionmentioning
confidence: 99%